Effectiveness of Tera Gymnastics and Healthy Heart Gymnastics on Blood Pressure Among Elderly With Hipertension in Sinomwidodo Village, Tambakromo Subdistrict, Pati District - Rofika, Ana; Yuniastuti, Ari (Public Health Perspective Journal, 2018)
The elderly are at high risk for degenerative diseases. Hypertension occupies the largest proportion of all degenerative diseases reported. Gymnastics Tera and Healthy Gymnastics are one of the nonpharmacology efforts to suppress Hypertension. The purpose of this study was to determine the effectiveness of Gymnastics Tera and Healthy Gymnastics Against Blood Pressure on Hypertensive Elderly. This research uses a quasi experiment method with Nonequivalent control group design. The population in this study is all elderly who suffer from Hypertension in Sinomwidodo Village Tambakromo Subdistrict, Pati Regency which according to criteria amounting to 35 elderly. Sampling with Purposive Sampling technique and sample size is determined by Slovin formula. The sample is 32 respondents with the provision of 11 people tera gymnastics group, 11 people healthy heart gymnastic group and 1o people control group. The results showed that after the intervention there was a significant effect between the group of Gymnastics Tera and Healthy Gymnastics compared with the control group with the measurement of mercury p-value (<0.05). There was no significant difference from the comparison of the post-test value of gymnastic exercise of Tera and Healthy Heart gymnastic to systolic and diatolic blood pressure in elderly hypertension p-value (> 0.05). Conclusion Gymnastics Tera and Healthy Gymnastic Gym are effective in lowering blood pressure in hypertensive elderly. The effectiveness of gymnastics Tera and Healthy Heart gymnastics are the same.